Hacia la construcción de un modelo interpretativo de las formas de rechazo en contra de las minorías religiosas en México: el caso del Protestantismo - Gervasi, Francesco (Comparative Cultural Studies: European and Latin American Perspectives, 2016)
The two main objectives of this paper are to describe acts of intolerance towards religious minorities in Mexico and build an interpretative model of the forms of racism that occur in these acts, focusing on the case of Protestantism. The methodological approach is qualitative and scope of the research is descriptive and exploratory. The results highlight that cultural racism against Mexican Protestants is institutionalized, differentialist, with origins of the violence of identity type (defensive) and social. The findings indicate the need to develop more efficient mechanisms in defense of religious diversity that have been used to date, to aspire to really build societies based on tolerance and, consequently, in the peaceful coexistence of differences.